Genetic algorithm based for optimizing filter design / Rohana Awang Ahmed - Awang Ahmed, Rohana (2000)
Filter design is usually a long and complicated process. The process involves a lot of computational work and mistakes are easily made. There is also possibility that the design does not meet specification thus forcing the process to be repeated. This project describe how Genetic Algorithm (GA) could be used to optimize the process of designing analog filter by considering such as magnitude response. The aim is to reduce the cost by reducing the filter order. Different type of filter such as Chebyshev, Inverse Chebyshev, Butterworth and Elliptical filter are considered. The transfer function of the network are obtained in a standard form. The conventional filter design technique is adapted in writing a MATLAB program using the Signal Processing Toolbox. GA is then implemented using the Genetic Algorithm Toolbox (GAOT). The result of using GA based methods are then compared to conventional design technique. Its provides an alternative means in filter design.